Control of Soil Erosion in Mzinga River Catchment In the Uluguru Mountains, Tanzania: Approaches and Practices - Mulengera, M. K.; Lulandala, L. L. L.; Maliondo, S. M.; Maerere, A. P.; Temu, R. P. C.; Bengesi, C. P. Msuya; Mvena, Z. S. K. (Tanzania Journal for Population studies and Development, 2009)
Soil erosion is a serious problem in Tanzania that leads to land degradation and rapid siltation of water reservoirs and water supply structures. This paper presents findings from a project initiated in 2003/2004 to rehabilitate the Mzinga River Catchment. The objective of the project was to rehabilitate the highly degraded catchment in order to improve peoples’ economic well being by imparting knowledge of raising tree seedlings in nurseries, growing forest and fruit trees, practicing agroforestry, and by establishing mechanical conservation works. The catchment conservation approach adopted was land user free choice in collaboration with community conservation committee and other key stake holders. Soil erosion measurements were done on fields, fallow lands, and semi-natural vegetation areas to monitor land use practices that contribute greatly to catchment degradation. Sediment yield modelling was done to determine rates of sediment yields from the catchment. The study results show very high soil erosion rates (up to more than 33 tons/ha) on agricultural lands, and sediment yields from the Mzinga river catchment of about 17 tons/ha per year. The study showed that conservation activities need extension to overcome the bad historical experiences of the communities in the catchment area, and to have more farmers adopting appropriate soil conservation measures after demonstrated increased productivity and economic benefits that will be achieved through good land husbandry practices and planted forest and fruit trees.